Leaders Eat Last: Why Some Teams Pull Together and Others Dont - Simon Sinek (Penguin Group, 2014)
Imagine a world in which majority of people wake up inspired to go to work, feel safe when they are and return home feeling fulfilled by the work thry do. The fascinating research and true stories in this book prove that leaders who are willing to eat last are rewarded with deeply loyal, inspired and effective colleagues its amazing how well it works.